Autonomous nervous system and cardiac arrhythmias in patients with recurrent atrial fibrillation: long-term electrocardiogram monitoring data - A. V. Vetluzhsky; I. G. Fomina (Кардиоваскулярная терапия и профилактика)
Aim. To study combined cardiac arrhythmias (CCA) and heart rate variability (HRV) in patients with recurrent atrial fibrillation (AF). Material and methods. In 41 patients with verified recurrent AF and 41 AF-free patients, 24 and/or 48-hour electrocardiogram monitoring (24hM, 48hM) was performed. Results. In 48hM, serious and life-threatening CCA (atrio-ventricular blocks, brief ventricular tachycardia episodes, frequent ventricular extrasystoles, asystolia episodes) were registered more often than in 24hM. In AF patients, HRV was significantly reduced, due to sympathetic activity of autonomous nervous system. Conclusion. 48hM could be used in patients with recurrent AF for CCA diagnostics. HRV reduction, typical for these patients, should be taken into account in selecting therapeutic strategies.